FASHIONING INCLUSIVITY: THE DYNAMIC CONNECTION BETWEEN BODY MASS INDEX AND READY-TO-WEAR CHOICES IN YOUNG AFRICAN AMERICAN FEMALES - Johnson, Elizabeth M.; Rodriguez, Maria A. (Journal of Current Research and Review (JCRR), 2024)
This abstract explores the intricate relationship between clothing preferences, body image perceptions, and the evolving physical body sizes of individuals. Clothing is not merely a covering but is intricately woven into the fabric of self-expression, serving as a tool for individuals to either enhance or conceal their body images. Consumers seek not only comfort in their attire but also aspire to present an idealized body image to the world. Rooted in the concept that clothing is a second skin, individuals make choices based on their desire to achieve an ideal body image, often characterized by slenderized and elongated appearances. This pursuit is not solely driven by physical body types but is strongly linked to self-perceived body images, reflecting the psychological impact of clothing on one's identity and self-esteem. The narrative contextualizes this phenomenon against the backdrop of the significant increase in physical body sizes over the last five decades, attributed to factors such as overeating and sedentary lifestyles. Despite this shift in physicality, clothing retailers predominantly rely on standard sizes based solely on physical body measurements, neglecting the psychological influence of weight on individuals' perceptual body images. The abstract underscores the critical need for a paradigm shift in the fashion industry, urging clothing retailers to consider weight as a pivotal factor in sizing standards. By recognizing the psychological impact of weight on individuals' self-perceptions, the fashion industry can align more closely with the diverse and evolving body images of consumers.